”Der er langt til Himlen og Evropa er langt borte”. Den afrikanske diskurs i dansk rejselitteratur - Schab, Sylwia (My University, 2011)
The article attempts to discuss two examples of Danish literary discourse on former Danish colonies on the Gold Coast (Africa). Sophie Petersen’s travel books “Danmarks gamle Tropekolonier”, 1946 (The former Danish Tropic Colonies) and “Vore gamle Tropekolonier”, 1948 (Our former Tropic Colonies) and Thorkild Hansen’s documentary novel “Slavernes Kyst”, 1967 (The Coast of the Slaves) have been analyzed as texts that re- veal a part of the Danish colonial and postcolonial (self-)reflection and consciousness. The literary representations of Africa given in the aforementioned books reflect the Danish nation-building project in the respective historical, political and mental contexts (during the Second World War and in the sixties). Petersen and Hansen apply different writing strategies (rhetorical as well as discursive) in their presentations of the Danish history of the Gold Coast, and they seem to represent rather dissimilar approaches to this topic. As a conclusion, the author of the article attempts to answer the question about the role of the African representations in the Danish self-understanding as a nation.
"There is a long way to heaven, and Europe is far away." African discourse in the Danish travel literature
Keywords: Danske kolonier i Afrika (Guldkysten); den eksotiske diskurs i dansk rejselitteratur; Thorkild Hansen; Sophie Petersen; danish colonies in Africa (the Gold Coast); the exotic discourse in Danish travel literature